ANALYSIS OF SUSTAINABLE DEVELOPMENT OF UZBEKISTAN'S REGIONAL ECONOMY - Junling, Shao (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
Uzbekistan is committed to integrating into economic globalization and actively participating in regional integration construction. From the beginning of the period President of the Republic of Uzbekistan Sh.Mirziyoyev has regarded the development of relations with neighboring countries and the strengthening of interregional economic cooperation as the priority of foreign relations of Uzbekistan's diplomatic and economic work, and is committed to building its own regional integration strategy. At the same time, Uzbekistan's economic strategy is of great significance to the stability and development of Central Asia, and will further promote the extensive international cooperation of the “The Belt and Road” initiative.